2013
DOI: 10.2215/cjn.00300113
|View full text |Cite
|
Sign up to set email alerts
|

Renal Clearance and Intestinal Generation of p-Cresyl Sulfate and Indoxyl Sulfate in CKD

Abstract: SummaryBackground and objectives p-Cresyl sulfate and indoxyl sulfate contribute to cardiovascular disease and progression of renal disease. Renal clearance of both solutes mainly depends on tubular secretion, and serum concentrations are widely dispersed for any given stage of CKD. From this information, it is inferred that estimated GFR is not a suitable proxy of the clearance of these solutes. Formal clearance studies have, however, not been performed to date.Design, setting, participants, & measurements Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
86
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 27 publications
2
86
1
Order By: Relevance
“…Indole and p-cresol, the precursors of indoxyl sulfate and p-cresol sulfate, are thought to be produced by different microbes, and prior studies have shown limited correlation between the generation rates of indoxyl sulfate and p-cresol sulfate both in healthy participants and hemodialysis patients (31,32). We found, however, that the changes in indoxyl sulfate and p-cresol sulfate in response to dietary fiber were closely related, as depicted in Figure 2.…”
Section: Discussionmentioning
confidence: 54%
“…Indole and p-cresol, the precursors of indoxyl sulfate and p-cresol sulfate, are thought to be produced by different microbes, and prior studies have shown limited correlation between the generation rates of indoxyl sulfate and p-cresol sulfate both in healthy participants and hemodialysis patients (31,32). We found, however, that the changes in indoxyl sulfate and p-cresol sulfate in response to dietary fiber were closely related, as depicted in Figure 2.…”
Section: Discussionmentioning
confidence: 54%
“…19 Because these two solutes are less well cleared than HA and CMG 25 and because their excretion variability correlates strongly with filtration, they may not represent independent secretory solutes, despite having somewhat more a priori information regarding their primary transporters. 18,26,27 They may also be subject to a high degree of protein binding, reducing availability for proximal tubule transport and thereby, possibly leading to measurement error in solute clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Although it can be hypothesized that this imbalance is caused by differences in phase 2 metabolism, possibly influenced by renal dysfunction, this has not been studied to date. Furthermore, renal handling of PCG is unknown but may be different compared with PCS, which mainly depends on tubular secretion (13)(14)(15)(16). In addition, although it is well established that serum PCS is highly protein bound (17,18), protein binding characteristics of serum PCG are less clear, possibly contributing to differential renal clearance of PCS and PCG.…”
Section: Introductionmentioning
confidence: 99%